Prospek dan tantangan kabupaten layak anak (KLA) di kabupaten Cirebon - Syaeful Bakhri; Cucu Herawati; Wardah Nuroniyah (Yinyang: Jurnal Studi Islam Gender dan Anak, 2020)
In the development of KLA in Indonesia, there has not been a single region in West Java Province that has won the title of child-friendly regency/city. Cirebon Regency itself has succeeded in achieving the title of Child-Friendly City (KLA) in the Primary category in 2015. This study aims to determine the prospects and challenges of the Cirebon Regency towards a Child-Friendly Regency with a better grade. The research approach used is a type of qualitative descriptive research with data collection methods in-depth interviews, data processed through SWOT analysis. The results of the study show a combination of strategies with the highest priority, namely Strength – Opportunity (SO), followed by Weakness – Opportunity (WO), then Strength – Threat (ST), and Weakness – Threat (WT). With an interpretation that the intended strategy is how to maximize strength and opportunities to support the running of child-friendly regional action plans in the Cirebon Regency.